2009
DOI: 10.1103/physrevlett.103.027004
|View full text |Cite
|
Sign up to set email alerts
|

Origin of the Inverse Spin Switch Effect in Superconducting Spin Valves

Abstract: The resistance of a ferromagnet/superconductor/ferromagnet (F/S/F) spin valve near its superconducting transition temperature, Tc, depends on the state of magnetization of the F layers. This phenomenon, known as spin switch effect (SSE), manifests itself as a resistance difference between parallel (RP ) and antiparallel (RAP ) configurations of the F layers. Both standard (RP > RAP ) and inverse (RP < RAP ) SSE have been observed in different superconducting spin valve systems, but the origin of the inverse SS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
62
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(66 citation statements)
references
References 35 publications
4
62
0
Order By: Relevance
“…Before considering an explanation for this behaviour involving the generation and diffusion of spin-triplet pairs, we will first discuss possible effects arising from fringing fields [26][27][28][29] and spin imbalance 30 in Nb, factors that have been advanced as enhancing T C in the P state. In the fringing fields scenario, T C could be suppressed as a consequence of magnetic dipolar coupling between the two F (Py) layers, which introduces flux into the superconductor (Nb).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Before considering an explanation for this behaviour involving the generation and diffusion of spin-triplet pairs, we will first discuss possible effects arising from fringing fields [26][27][28][29] and spin imbalance 30 in Nb, factors that have been advanced as enhancing T C in the P state. In the fringing fields scenario, T C could be suppressed as a consequence of magnetic dipolar coupling between the two F (Py) layers, which introduces flux into the superconductor (Nb).…”
Section: Discussionmentioning
confidence: 99%
“…In the fringing fields scenario, T C could be suppressed as a consequence of magnetic dipolar coupling between the two F (Py) layers, which introduces flux into the superconductor (Nb). This suppression should be greatest close to the coercive field of the F layers when the density of the fringing fields from Néel domain walls is maximized 28 . This explanation cannot, however, explain our results, as samples without Ho show a well-defined decrease in R at coercivity and in the AP state, which translates into an enhancement rather than a decrease of T C (similar results are reported in ref.…”
Section: Discussionmentioning
confidence: 99%
“…This was explained as either due to enhanced reflection of spin-polarized quasiparticles ͑a mechanism not present in the calculations with equal spin subbands͒, 11 or to the effects of stray fields from domain walls. 10,[12][13][14] The difference between the observations of the standard and the inverse effects appears to be that those experiments finding standard behavior make use of an antiferromagnetic pinning layer in order to have one layer with fixed, and one layer with a freely rotating magnetization, while the reports on the inverse effect use a difference of d F or different materials for both layers in order to create a difference in coercive fields and thereby a field range where the magnetizations are AP. The pinning layer suppresses domain formation, and, in particular, the work of Zhu et al showed that if, in samples with a pinning layer, the free layer is brought in a domain state, the standard spin-valve effect is lost.…”
Section: Introductionmentioning
confidence: 96%
“…The pinning layer suppresses domain formation, and, in particular, the work of Zhu et al showed that if, in samples with a pinning layer, the free layer is brought in a domain state, the standard spin-valve effect is lost. 10 Focusing now on samples without pinning layer, almost all investigations were performed on ͑millimeter͒ large samples, where large amount of domains were present during the transition from the P to the AP state. In the work of Rusanov et al, samples were structured down to micrometer size, and the switching of the magnetization was instantaneous, giving blocklike variations in the resistance, and suggesting that a clear P to AP switch was obtained.…”
Section: Introductionmentioning
confidence: 99%
“…Before concluding that the trend of T C on θ can be explained on the basis of spin-triplet pair generation, we must first rule out the possibility that fringing fields from the PSV are suppressing T C (a particular issue in F-S-F structures [35,36]) or that the proximity effect is due to singlet pairs.…”
mentioning
confidence: 99%